2022
DOI: 10.3390/cancers14112736
|View full text |Cite
|
Sign up to set email alerts
|

Memantine in the Prevention of Radiation-Induced Brain Damage: A Narrative Review

Abstract: Preserving cognitive functions is a priority for most patients with brain metastases. Knowing the mechanisms of hyperglutamatergic neurotoxicity and the role of some hippocampal areas in cognitive decline (CD) led to testing both the antiglutamatergic pharmacological prophylaxis and hippocampal-sparing whole-brain radiotherapy (WBRT) techniques. These studies showed a relative reduction in CD four to six months after WBRT. However, the failure to achieve statistical significance in one study that tested memant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 200 publications
0
2
0
Order By: Relevance
“…Concerns about side effects appear to play a minor role for German-speaking ROs (3 %), compared to ROs in the US (22.4 %) [17] . Further increasing pre-clinical and clinical evidence regarding the mechanism of action of memantine may gradually alter current opinions [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about side effects appear to play a minor role for German-speaking ROs (3 %), compared to ROs in the US (22.4 %) [17] . Further increasing pre-clinical and clinical evidence regarding the mechanism of action of memantine may gradually alter current opinions [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Memantine, an N-methyl-D-aspartate receptor antagonist, has been proved to reduce the neurocognitive dysfunctions after WBRT. Brain irradiation, especially neural stem cells of hippocampi, leads to cognitive deterioration as a result of the radiation-induced accelerated neurosclerosis, microangiopathy, and infarction [54,55]. Study of RTOG 0614 revealed that memantine as a pharmacological neuroprotector was well tolerated by patients and resulted in good neurocognitive function preservation in patients receiving WBRT with memantine compared to only WBRT at 24 weeks observation follow-up (p = 0.0041) [52].…”
Section: Pharmacological Neuroprotection During Wbrtmentioning
confidence: 99%
“…To mitigate radiation injury, various approaches are being explored. Radioprotective drugs like memantine 15 , vitamins 16 , amifostine 17 , 18 (NCT00040365), melatonin 19 , 20 (NCT03716583), evosk 21 , and trixiera 21 , 22 (NCT02334345) are explored. Advances in imaging and positioning techniques 23 provide a foundation for accurate RT.…”
Section: Introductionmentioning
confidence: 99%